'Dark Choreography' of the Johannesburg Holocaust and Genocide Centre. (17th February 2020) - Sassen, Robyn
Abstract : In 'Dark Choreography' of the Johannesburg Holocaust and Genocide Centre, Robyn Sassen writes about how the designer and curator of a South African museum that deals with mass killing in Europe and in Africa have imposed an ad hoc choreography for the visitor, encouraging them to move their bodies in response to the dark ecology of a world turned by hate. The permanent display of the JHGC, which was founded by Tali Nates in March of 2019, was designed by Clive van den Berg and curated by Lauren Segal. This display, considering the dystopia of genocides and the traditions of museums reflecting trauma, confronts the viewer with words, images, sounds and objects that resonate with people murdered for the sin of being born to an unpopular tribe. Based on personal interviews with van den Berg and Segal, this article explores significant curatorial decisions taken that distinguishes this museum from others like it in the rest of the world with a similar set of display priorities. The dark energy of a museum about genocide inverts the relationship of audience and display, forcing the visitor to engage in a kind of 'dark choreography' of power and poetry, information, taboo and horror.